Music Therapy During COVID-19: Changes to the Practice, Use of Technology, and What to Carry Forward in the Future - Agres, Kat R.; Foubert, Katrien; Sridhar, Siddarth (Frontiers in Psychology, 2021)
In recent years, the field of music therapy (MT) has increasingly embraced the use of technology for conducting therapy sessions and enhancing patient outcomes. Amidst a worldwide pandemic, we sought to examine whether this is true to an even greater extent, as many music therapists have had to approach and conduct their work differently. The purpose of this survey study is to observe trends in how music therapists from different regions around the world have had to alter their practice, especially in relation to their use of technology during the COVID-19 pandemic, because of limited options to conduct in-person therapy due to social distancing measures. Further, the findings aim to clarify music therapists’ perspectives on the benefits and limitations of technology in music therapy, as well as online MT. In addition, this survey investigated what changes have been necessary to administer music therapy during COVID-19, in terms of virtual therapy and online tools, and how the changes made now may affect music therapy in the future. We also explored music therapists’ views on whether special technology-focused training might be helpful to support the practice of MT in the future. This is also the first survey, to our knowledge, to break down opinions of and trends in technology use based on geographical region (North America, Europe, and Asia), and several noteworthy differences were apparent across regions. We hope our findings provide useful information, guidance, and a global reference point for music therapists on effectively continuing the practice of music therapy during times of crisis, and can encourage reflection and improvement in administering music therapy.